Preparation method of polyurethane carbon material / graphene composite material
Through the polyurethane foam/transition metal composite system heat treatment at high temperature, porous composite carbon material is generated and peeled off to obtain polyurethane carbon material/graphene composite material, solving the problems of high cost and low electrochemical performance of existing carbon-based energy storage materials, and achieving a supercapacitor electrode material with high specific surface area and excellent electrochemical performance.
Patent Information
- Application Number
- CN202510002482.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-04
AI Technical Summary
The existing carbon-based energy storage materials have high cost and low electrochemical performance, making them difficult to meet the needs of high energy density, high power density, long cycle life, low cost, good safety performance and environmentally friendly.
The polyurethane foam/transition metal composite system is used to heat treatment under a gaseous hydrocarbon/hydrogen/argon mixed gas to generate porous composite carbon material, and the polyurethane carbon material/graphene composite material is obtained by in-situ peeling.
It achieves high specific surface area and excellent electrochemical performance. It is suitable for flexible supercapacitor electrodes, has higher specific capacitance, good rate performance and cycle stability, and is simple in process and has a wide range of raw materials.
Smart Images

Figure BDA0005225770380000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy materials, and specifically relates to a method for preparing a polyurethane carbon material / graphene composite material, which can be used for porous electrode materials. Background Art
[0002] In order to reduce the use of petroleum fuels and reduce carbon dioxide emissions, many countries have increased their research and investment in hybrid electric vehicles and electric vehicles. The most critical part of hybrid electric vehicles and electric vehicles is the power system, so it is particularly important to develop efficient energy storage devices with high energy density, high power density, long cycle life, low cost, good safety performance and environmental friendliness.
[0003] Among the numerous energy storage electrode materials, porous carbon-based three-dimensional network structures have attracted widespread attention with their excellent conductivity, high specific surface area, and excellent electrochemical stability, and have become a research hotspot in this field. More importantly, due to the spatiality of the carbon-based three-dimensional network structure, it can be directly used as a flexible electrode material for energy storage devices, thereby expanding the application field of energy storage devices. The preparation of porous carbon-based materials usually requires a carbon precursor. After a special heat treatment, the precursor is obtained to obtain a carbon-based material. General precursors include: asphalt, phenolic resin, polyurethane, biomass materials, etc. The carbon content, structural temperature resistance, and heteroatom content of the precursor directly affect the final carbon yield and electrochemical performance. Therefore, how to obtain a porous three-dimensional carbon material with a simple method, large specific surface area, and excellent electrochemical performance is of great significance. Summary of the invention
[0004] The purpose of the present invention is to provide a porous carbon material with polyurethane resin as a precursor and a preparation method thereof, that is, a preparation method of a polyurethane carbon material / graphene composite material. The preparation method has low cost and has excellent specific surface area and electrochemical performance as an electrode material.
[0005] In order to achieve the above purpose, the present invention adopts the following process scheme:
[0006] A method for preparing a polyurethane carbon material / graphene composite material comprises the following steps:
[0007] 1) Preparing a polyurethane foam / transition metal composite system;
[0008] 2) heat-treating the polyurethane foam / transition metal in a gaseous hydrocarbon / hydrogen / argon mixed gas to obtain a porous composite carbon material / transition metal composite system;
[0009] 3) In-situ exfoliation of the porous composite carbon material / transition metal is performed to finally obtain a polyurethane carbon material / graphene composite material.
[0010] The preparation method of the polyurethane foam / transition metal composite system in the present invention is as follows: the temperature of isocyanate and combined polyether polyol is controlled at 20-28° C., mixed in a certain proportion, stirred at 2000 r / min for 8-20 seconds to obtain a mixed solution, and before any reaction occurs, the transition metal is immersed in the mixed solution and ultrasonically treated for 3-5 minutes, so that the polyurethane foam is uniformly infiltrated into the interior of the transition metal.
[0011] In the present invention, the isocyanate is selected from polyisocyanates with NCO functionality ≥ 2, preferably one or more of aromatic diisocyanates, more preferably polymethylene polyphenyl polyisocyanate. Its viscosity is 130-800mPa·s (25°C), including but not limited to PM-200, PM-400, PM-700, PM-2010 and other brands of Wanhua Chemical.
[0012] The combined polyether polyol component of the present invention is preferably a low viscosity, high fluidity system with a viscosity of 150-400 cp (25° C.) and a milky time of 3-10 min, preferably Wanhua Chemical RH9008 and RH9002 series products.
[0013] In the present invention, the mass ratio of isocyanate to combined polyether polyol is preferably 1.5-2:1.
[0014] In the present invention, the transition metal is preferably in the form of porous foam, including but not limited to one of foamed iron, foamed platinum, foamed nickel, foamed copper, and foamed cobalt, preferably foamed nickel and foamed copper.
[0015] In the present invention, step 2) the obtained polyurethane foam / transition metal is placed in a tubular furnace at 800-1000°C, and heat treated for 4-8h in a gaseous alkane / hydrogen / argon mixed gas, and the gaseous hydrocarbons as a carbon source are cracked at high temperature, and the generated carbon atoms penetrate into the transition metal substrate, and then the temperature is rapidly reduced at 4-8°C / min, at which time the carbon atoms are precipitated on the surface of the transition metal to form a single layer of graphene; the polyurethane foam is simultaneously carbonized at high temperature to obtain a polyurethane foam carbon material / graphene / transition metal composite porous material (porous composite carbon material / transition metal composite system).
[0016] The gaseous alkane described in the present invention includes but is not limited to one of methane, ethylene and acetylene, preferably methane gas, and the relative volume flow ratio of gaseous alkane / hydrogen / argon gas is 1-2:1-2:1, preferably 1-1.5:1-1.5:1.
[0017] In the present invention, in step 3), the porous composite carbon material / transition metal composite system obtained in step 2) is immersed in a polymethyl methacrylate (hereinafter referred to as PMMA) solution for 0.5-6 hours, then placed in a 50-180°C oven for baking for 0.5-4 hours and then cooled to room temperature to solidify the PMMA and closely adhere to the composite porous material.
[0018] The obtained PMMA-covered porous composite carbon material / transition metal composite system is immersed in a metal etchant for 0.5-5 hours to completely etch the metal, washed with deionized water for 3-5 times, and dried at 30-80°C for 1-6 hours to obtain a PMMA-covered porous composite carbon material / transition metal composite system.
[0019] The polyurethane foam carbon material / graphene / transition metal composite porous material is transferred from the transition metal substrate through a certain etching process. A layer of PMMA is spin-coated on the polyurethane foam carbon material / graphene / transition metal composite porous material, and the composite porous material covered with the transfer medium is placed in a metal etchant for immersion. After the metal is completely etched, the transfer medium and the porous composite material float on the surface of the etching solution, and then washed with acetone, dried, and then the material is placed in an inert gas at a high temperature of 600°C-1000°C for calcination for 0.5-6h, while removing PMMA, further improving the graphitization degree of the carbon material, and finally obtaining a polyurethane carbon material / graphene composite material.
[0020] Preferably, the PMMA is a conventional powder material purchased on the market, which is dissolved in ethyl acetate or phenyl ether at a concentration of 20-60%, and stirred for 1-6 hours to completely dissolve the PMMA powder in the solution.
[0021] Preferably, the inert atmosphere includes but is not limited to one or more of nitrogen, argon and / or helium.
[0022] Preferably, the metal etchant includes but is not limited to acids that can dissolve transition metals, such as 36-38% hydrochloric acid, 95-98% sulfuric acid, 60-68% nitric acid, preferably 36-38% hydrochloric acid.
[0023] The specific surface area of the polyurethane carbon material / graphene composite material obtained by the present invention is as high as 1000-1654m 2 / g, the specific capacitance can reach 150-350F / g, and the rate performance can be maintained above 90% after 10,000 charge and discharge cycles.
[0024] The polyurethane carbon material / graphene composite material of the present invention can be used as an electrode material for supercapacitors alone or in combination with other electrode materials to prepare nano-composite electrode materials. Other electrode materials include but are not limited to one or more of carbon fiber, graphene, carbon nanotubes, metal oxides, and conductive polymers.
[0025] The positive effect of the present invention is that the present invention discloses a method for preparing a porous composite carbon material by chemical vapor deposition using polyurethane foam / transition metal as a matrix. The polyurethane foam is pre-compounded with a transition metal by utilizing its infiltration foaming characteristics, and is used as a matrix to perform heat treatment under a mixture of gaseous alkanes / hydrogen / argon. Graphene is grown in situ on the surface of the transition metal, and the polyurethane foam is carbonized synchronously. After the transition metal is subsequently removed, a porous carbon material with different pore size distributions is finally obtained. The carbon material has extremely high specific surface area and electrochemical properties, can be directly used as a flexible supercapacitor electrode, and has higher specific capacitance, good rate performance and cycle stability. This treatment method is simple and easy to operate, and the raw materials are widely available. It successfully solves the problems of high cost and low electrochemical performance of current carbon-based energy storage materials, and conforms to the environmentally friendly design concept. DETAILED DESCRIPTION
[0026] The following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.
[0027] The following descriptions of the instruments used for the detection in the comparative examples are as follows:
[0028] Total specific surface area: The instrument is a fully automatic specific surface area analyzer, model: Autosorb-iQ2, and the instrument manufacturer is Quantachrome Company of the United States.
[0029] Capacitance: The instrument is an electrochemical workstation, model CHI 660C, manufactured by Shanghai Chenhua Instrument Company.
[0030] The raw materials used in the following examples and comparative examples are described as follows:
[0031] Isocyanate: Wanhua Chemical PM200 (viscosity 200cp, NCO functionality 2);
[0032] Combined polyether polyol: Wanhua Chemical RH9008-101 (viscosity 185cp, milky time 4.5min);
[0033] Nickel foam / copper foam: Wuzhou Sanhe New Material Technology Co., Ltd.;
[0034] Cobalt foam: Suzhou Maozhen New Material Technology Co., Ltd.;
[0035] Hydrochloric acid / ethyl acetate: Aladdin;
[0036] PMMA: Evonik.
[0037] Example 1
[0038] Preparation of polyurethane foam / foam nickel composite system: PM200 and RH9008-101 were controlled at 25°C, mixed at a mass ratio of 1.5:1, and stirred at 2000 r / min for 15 seconds, and foam nickel was placed in the mixed solution, ultrasonically vibrated for 3 minutes, and the polyurethane reaction was matured for 24 hours to obtain a polyurethane foam / foam nickel composite system;
[0039] Preparation of a porous composite carbon material / foam nickel composite system: placing the polyurethane foam / foam nickel obtained above in a 900°C tubular furnace, heat-treating for 6 hours in a methane / hydrogen / argon mixed gas at a relative volume flow ratio of 1.5:1:1, and then rapidly cooling at 6°C / min to obtain a porous composite carbon material / foam nickel composite system;
[0040] Prepare PMMA solution: dissolve 50 g PMMA powder in 100 ml ethyl acetate solution and stir for 4 h to completely dissolve the PMMA powder.
[0041] Preparation of polyurethane carbon material / graphene composite porous carbon material: Soak the porous composite carbon material / nickel foam obtained above in PMMA solution for 3 hours, then bake it in a 120°C oven for 2 hours and cool it to room temperature, then soak it in a 36% hydrochloric acid solution for 3 hours, take it out and wash it with deionized water 3 times, then place it in a 60°C oven for 4 hours to dry, and obtain a polyurethane foam carbon material / graphene composite porous material covered and supported by PMMA. The above material is calcined at 800°C for 4 hours in a nitrogen atmosphere to finally obtain a polyurethane carbon material / graphene composite material.
[0042] Preparation of supercapacitor electrode materials and electrochemical performance testing: The porous composite carbon material prepared above has a specific surface area of 1640 m 2 / g, 2mg of it was placed in two pieces of nickel foam as the working electrode, metal Pt as the counter electrode, Hg / HgO electrode as the reference electrode, the electrolyte was 6M KOH, the charge and discharge cut-off voltage was -1-0V, and when the charge and discharge current was 0.1Ag-1, its specific capacity was 343F / g. After 10,000 cycles, the capacity retention rate was 96.8%.
[0043] According to the raw materials and processes in Table 1, the operation of Example 1 was repeated to prepare and test the porous carbon materials of Examples 2-4 and Comparative Examples 1-2, respectively.
[0044] Comparative Example 1
[0045] Preparation of graphene / nickel foam composite system: placing nickel foam in a 900°C tubular furnace, heat treating for 6 hours in a methane / hydrogen / argon mixed gas at a relative volume flow rate of 1.5:1:1, and then rapidly cooling at 6°C / min to obtain a graphene / nickel foam composite system;
[0046] Preparation of graphene porous carbon material: The graphene / nickel foam obtained above was immersed in a PMMA solution for 3 hours, then baked in a 120°C oven for 2 hours and cooled to room temperature, and then immersed in a 36% concentration hydrochloric acid solution for 3 hours. After taking it out, it was washed with deionized water 3 times, and then placed in a 60°C oven for 4 hours to dry. The above material was placed in a nitrogen atmosphere and calcined at 800°C for 4 hours to finally obtain a porous graphene material.
[0047] The electrochemical properties are shown in Table 2.
[0048] Comparative Example 2
[0049] Preparation of polyurethane foam carbon material: PM200 and RH9008-101 were mixed at a mass ratio of 1.5:1 at 25°C, stirred at 2000 r / min for 15 seconds, and reacted for 24 hours to obtain polyurethane foam;
[0050] Preparation of polyurethane foam carbon material: The polyurethane foam obtained above was placed in a 900°C tubular furnace, and heat treated for 6 hours in a methane / hydrogen / argon mixed gas with a volume relative flow rate of 1.5:1:1, followed by rapid cooling at 6°C / min, and then the above material was calcined at 800°C for 4 hours in a nitrogen atmosphere to finally obtain a polyurethane carbon material.
[0051] The electrochemical properties are shown in Table 2.
[0052] Table 1 Key raw materials and process parameters of Examples 1-4 and Comparative Examples 1-2
[0053]
[0054] Table 2 Performance test results of porous carbon materials prepared in Example 2
[0055] <![CDATA[Total specific surface area (m 2 g -1 )]]> <![CDATA[Specific capacitance (F g -1 )]]> Cycle stability / % Example 1 1640 343 96.8 Example 2 1570 314 95.1 Example 3 1561 309 94.9 Example 4 1507 298 94.3 Comparative Example 1 1234 256 92.4 Comparative Example 2 1092 159 89.1
[0056] The charge and discharge cut-off voltage of the above test is -1 to 0 V. The specific capacitance is tested at a current density of 0.1 A / g, and the cycle stability refers to the retention rate of the specific capacitance after 10,000 charge and discharge cycles at 0.1 A / g.
[0057] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A method for preparing a polyurethane carbon material / graphene composite material, characterized in that: The following steps are involved: 1) Preparing a polyurethane foam / transition metal composite system; 2) heat-treating the polyurethane foam / transition metal in a gaseous hydrocarbon / hydrogen / argon mixed gas to obtain a porous composite carbon material / transition metal composite system; 3) In-situ exfoliation of the porous composite carbon material / transition metal is performed to finally obtain a polyurethane carbon material / graphene composite material.
2. The preparation method according to claim 1, characterized in that: The transition metal is in the form of foam, preferably one of foamed iron, foamed platinum, foamed nickel, foamed copper, and foamed cobalt, and more preferably foamed nickel or foamed copper.
3. The preparation method according to any one of claims 1 to 2, characterized in that: The preparation method of the polyurethane foam / transition metal composite system is as follows: the temperature of the isocyanate and the combined polyether polyol is controlled at 20-28°C, and the mixture is stirred for reaction for 8-20s to obtain a mixed solution. Before the reaction occurs, the transition metal is immersed in the mixed solution and ultrasonically treated for 3-5min, so that the polyurethane foam is uniformly infiltrated into the interior of the transition metal; preferably, the mass ratio of the isocyanate to the combined polyether polyol is 1.5-2:
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step 2), the polyurethane foam / transition metal is heat treated in a tubular furnace at 800-1000°C for 4-8h and then rapidly cooled at 4-8°C / min; preferably, the gaseous alkane comprises one of methane, ethylene, and acetylene, preferably methane gas, and the relative volume flow ratio of the gaseous alkane / hydrogen / argon gas is 1-2:1-2:1, preferably 1-1.5:1-1.5:
1.
5. The preparation method according to any one of claims 1 to 4, characterized in that: Step 3) is to soak the porous composite carbon material / transition metal composite system in a polymethyl methacrylate solution for 0.5-6 hours and then bake it to solidify the PMMA and make it tightly adhere to the composite porous material, then soak it in a metal etchant to completely etch the metal, then wash and dry it, and finally calcine it to obtain a polyurethane carbon material / graphene composite material.
6. The preparation method according to claim 5, characterized in that: The baking temperature is 50-180°C and the baking time is 0.5-4h.
7. The preparation method according to claim 5 or 6, characterized in that: The metal etchant includes but is not limited to one of strong acids, preferably hydrochloric acid, sulfuric acid, and nitric acid; and / or, immersing in the metal etchant for 0.5-5 hours.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The calcination is carried out in an inert atmosphere, the calcination temperature is 600°C-1000°C, and the calcination time is 0.5-6h.
9. The polyurethane carbon material / graphene composite material prepared by the preparation method according to any one of claims 1 to 8, having a specific surface area of 1000-1654 m 2 / g, specific capacitance 150-350F / g, and rate performance maintained above 90% after 10,000 charge and discharge cycles.
10. Use of the polyurethane carbon material / graphene composite material prepared by the preparation method according to any one of claims 1 to 8 or the polyurethane carbon material / graphene composite material according to claim 9 as an electrode material for a supercapacitor, alone or in combination with other electrode materials to prepare a nano-composite electrode material, wherein the other electrode materials include but are not limited to one or more of carbon fiber, graphene, carbon nanotubes, metal oxides, and conductive polymers.
Citation Information
Cited By
Filtering supercapacitor based on nanoparticle-shaped graphene / foam metal and preparation method thereof
CN120954896A
A nanoparticle graphene / foam metal-based filtering supercapacitor and a preparation method thereof
CN120954896B